The application of urbanise mokshapat edutainment (U.M.E) in teaching and learning for town & regional planning programme / Norhazlan Haron ... [et al.] - Haron, Norhazlan; Mohamad Bahari, Noor Ashikin; Sallehudin, Noor Syarafina; Abdullah Kamar, Muhamad Asri; Teriman, Suharto (2020)
Teaching and learning should escape from the traditional approach that only focuses on content and oneway learning. Hence Education 4.0 was introduced as a desired approach to learning that aligns itself with the fourth industrial revolution. UiTM then made an advance follow-up with Education 5.0 @ UiTM, with a vision where teaching and learning are supposed to be more flexible and adaptive. Many approaches have been used by lecturers to encourage active learning in class. These includes lectures and blended learning which integrate technology in learning. However, there are issues where students still face difficulties to understand the subjects they learnt especially when these subjects are related to facts and theories. The question is, does technology really help to encourage active learning in class? The objectives of this research are to develop an edutainment board game that integrates the knowledge of Town and Regional Planning as well as to promote active learning among students to increase their attention in class and understanding of the subject matter. The existence of traditional games including board games has increasingly been eroded, and over time these traditional games will be replaced by gadgets if educators and parents did not introduce them to students. The physical board game not only encourage students to be active in class, but it also encourages cooperation among themselves, hence strengthening their relationships.